Perception d’étudiants universitaires face à un service d’entraide - Losier, Francine; Ouellette, Jean-Guy (Canadian Journal of Counselling and Psychotherapy, 2011)
This article presents university students' perceptions of a Peer counselling program. The information needed was acquired among 172 students enrolled in various programs in education. The results demonstrated that the students were very well aware of the existence of the Peer counselling program. They considered that the diffusion of information at registration in September, the poster, the pamphlet, the presentation in class and the peer counselor him/herself were the most efficient means of transmitting information to the students. In addition, the students showed certain preferences concerning the area reserved for counselling, the availability of the peer counsellors and the person to consult in the event of a difficulty to resolve a problem. Finally, we conclude that